1990
DOI: 10.1039/p29900000025
|View full text |Cite
|
Sign up to set email alerts
|

Imines and derivatives. Part 23. Anomalous 1H NMR spectrum of N-[1-(1-naphthyl)ethylidene]-1-phenyl-2-propylamine: conformation in solution, atropisomerism and an X-ray crystal structure

Abstract: 5AG'H NMR spectra of the title imine in solution indicate the presence of three stereoisomers due to € / Z isomerism about the imino bond and atropisomerism about the 1 -naphthyl imino bond in the Zisomer. The most abundant Z-isomer, which was isolated in crystalline form, exhibits a highly unusual NMR signal at 6 5.9 assigned to a naphthyl proton cc to the imino group. The X-ray crystal structure reveals that this hydrogen atom is situated only 2.7 a above the face of the phenyl ring of the N-I -phenyl-2-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…−1.5 to −2.0 kcal mol −1 ). 10,11 The face tilted-T (c) which has been observed in our imino [12][13][14] and biaryl 15 model systems and in the cyclophanes reported by Kim et al, 16 Fukazawa et al 17 and Schladetsky Q4 et al 18 is a distortion of the T-structure (b) produced by limitations of the linker groups. It is probably not quite an energy minimum for the benzene dimer and therefore probably has a reduced interaction energy.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…−1.5 to −2.0 kcal mol −1 ). 10,11 The face tilted-T (c) which has been observed in our imino [12][13][14] and biaryl 15 model systems and in the cyclophanes reported by Kim et al, 16 Fukazawa et al 17 and Schladetsky Q4 et al 18 is a distortion of the T-structure (b) produced by limitations of the linker groups. It is probably not quite an energy minimum for the benzene dimer and therefore probably has a reduced interaction energy.…”
Section: Introductionsupporting
confidence: 60%
“…These distances are longer than most of those previously reported for molecules with face tilted-T geometry. 9,[12][13][14][15] The inter ring tilt angle A-C (36°) is also unusually low, hence the geometry lies slightly closer to a parallel displaced structure (tilt angle 0°) than a T-shaped structure (tilt angle 90°). The distance of Ho above the ring C plane is likely to increase as the tilt angle decreases from 90°in the T-structure to 0°in the parallel displaced structure.…”
Section: Papermentioning
confidence: 98%
See 2 more Smart Citations
“…Hamor et al [45] found that the E/Z exchange by rotation about the imino bond is slow on the NMR time scale. The most abundant Z isomer has been isolated, and the X-ray structure reveals that the hydrogen atom H1 is only 2.7 ä above the face of the phenyl ring C1 ± C6.…”
Section: Ch/p Interacting Systemsmentioning
confidence: 99%